2006
DOI: 10.1029/2005gl025588
|View full text |Cite
|
Sign up to set email alerts
|

New boundary conditions for the West Antarctic ice sheet: Subglacial topography beneath Pine Island Glacier

Abstract: Predictions about future changes in the Amundsen Sea sector of the West Antarctic ice sheet (WAIS) have been hampered by poorly known subglacial topography. Extensive airborne survey has allowed us to derive improved subglacial topography for the Pine Island Glacier basin. The trunk of this glacier lies in a narrow, 250‐km long, 500‐m deep sub‐glacial trough, suggesting a long‐lived and constrained ice stream. Two tributaries lie in similar troughs, others lie in less defined, shallower troughs. The lower basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
229
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(234 citation statements)
references
References 16 publications
5
229
0
Order By: Relevance
“…Satellite observations of relative tidal motion show that the PIG hinge line retreated by up to 25 km between 1992 and 2009 [Rignot, 1998b;Joughin et al, 2010]. This retreat corresponds to a reduction in ice thickness of around 90 m at the glacier terminus considering the recent geometry [Vaughan et al, 2006], a value that is consistent with direct observations of thinning acquired by satellite altimetry during the same period [Wingham et al, 2009].…”
Section: Introductionsupporting
confidence: 80%
See 2 more Smart Citations
“…Satellite observations of relative tidal motion show that the PIG hinge line retreated by up to 25 km between 1992 and 2009 [Rignot, 1998b;Joughin et al, 2010]. This retreat corresponds to a reduction in ice thickness of around 90 m at the glacier terminus considering the recent geometry [Vaughan et al, 2006], a value that is consistent with direct observations of thinning acquired by satellite altimetry during the same period [Wingham et al, 2009].…”
Section: Introductionsupporting
confidence: 80%
“…The progressive retreat of the PIG hinge line has occurred presumably as a result of changes in both the rate of ocean melting and the glacier surface slope, the latter occurring as a dynamical response to reduced grounding [Joughin et al, 2003;Payne et al, 2004]. Although a substantial bedrock peak occurs around 25 km inland of the present hinge-line position (Figure 3d), this feature does not straddle the entire glacier width [Vaughan et al, 2006], and relief to the south side of the glacier, in particular, slopes gently. However, although the hinge line has retreated since 2009, analysis of glacier velocities reveals that the glacier speed has yet to increase (I. Joughin, personal communication), which suggests that further dynamical imbalance has yet to occur.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…They are readily distinguishable in Antarctica by synthetic aperture radar measurements over time (Bamber et al, 2000). Several studies have shown that onset zones are conicident with a thermal boundary within the ice sheet, where cold slow-flowing ice becomes warmer, wet-based, and, hence, faster flowing (Engelhardt and Kamb, 1998;Bamber et al, 2000;Vaughan et al, 2006). Relatively few studies, to date, have identified palaeo-ice-stream onset zones in the landscape record.…”
Section: Bedform Evolution: the Signature Of An Ice-stream Onset Zone?mentioning
confidence: 99%
“…This has reduced the buttressing exerted by the ice shelf, leading to the acceleration of the ice stream and the ongoing retreat of the grounding line (GL) along the glacier's trunk observed since 1992 [17]. Today the GL lies over bedrock that has a steep retrograde slope [29] (Figure 1c) raising the possibility that PIG may already be engaged in an irrevocable retreat. ProvidedAssuming that ice flow is dominated * durand@lgge.obs.ujf-grenoble.fr 2 by basal sliding and lateral variation can be ignored, grounding lines located on retrograde slopes are always unstable [24,3], but in realistic, three-dimensional geometries lateral drag and buttressing in the ice shelf can act to prevent unstable retreat [9].…”
mentioning
confidence: 99%